1997
DOI: 10.1038/sj.ijo.0800388
|View full text |Cite
|
Sign up to set email alerts
|

Associations between body morphology and microalbuminuria in healthy middle-aged European, Maori and Pacific Island New Zealanders

Abstract: OBJECTIVE: To examine the relationship between albuminuria and measures of body morphology. DESIGN: Cross-sectional study of European, Maori and Paci®c Island workers aged 40 y and over. SUBJECTS: 3960 non-diabetic, non-hypertensive, non-lipidaemic, non-proteinuric middle-aged men and women. MEASUREMENTS: Height, weight, waist, hip, fasting and 2 h glucose, systolic and diastolic blood pressure, urinary creatinine and urinary albumin measurements. RESULTS: After adjusting for age and gender, the relative risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…Healthy middle aged Polynesian people have previously been shown to have higher rates of microalbuminuria and increased urinary protein forms part of the diagnostic criteria for PE. In the current study, Polynesian women had marginally higher urine albumin: creatinine ratio on enrolment but this was not different from the other ethnic groups [8][9][10]16]. It could be postulated that higher early pregnancy BMI and higher fasting glucose at enrolment underlie the influence of Polynesian ethnicity.…”
Section: Discussioncontrasting
confidence: 60%
“…Healthy middle aged Polynesian people have previously been shown to have higher rates of microalbuminuria and increased urinary protein forms part of the diagnostic criteria for PE. In the current study, Polynesian women had marginally higher urine albumin: creatinine ratio on enrolment but this was not different from the other ethnic groups [8][9][10]16]. It could be postulated that higher early pregnancy BMI and higher fasting glucose at enrolment underlie the influence of Polynesian ethnicity.…”
Section: Discussioncontrasting
confidence: 60%
“…Similarly, several studies have suggested a differential effect according to body morphology. [15][16][17][18][19][20] The prevalence of MA among the study subjects was lower than that reported for a study of the general population. [5][6][7] This is expected following the selection criteria for the study.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Studies of glucose-tolerant subjects suggested that IR is not always associated with MA. [12][13][14] Some studies suggested that abdominal obesity is independently associated with MA, [15][16][17][18][19][20] whereas others showed that abdominal obesity is not related to the albuminuria level. 12,13 The latter studies may have been biased by factors such as a small sample size and the former studies did not exclude subjects with high-normal blood pressure or hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the features that have been ascribed to the metabolic syndrome are more common in obese subjects, including dyslipidaemia, hypertension, elevations in levels of plasminogen activator inhibitor-1 3 and fibrinogen, 5 and microalbuminuria. 7 Furthermore, manifestations of endothelial dysfunction, such as impaired responses to endothelial nitric oxidemediated vasodilators 8 and to shear stress, 9 are found in obese subjects, improving with weight loss. 10 These observations suggest the existence of adipose-generated signals, which influence not only insulin action in skeletal muscle, and both insulin action and acute-phase activation in the liver, but also modulate endothelial cell function in conduit and resistance vessels and in capillaries.…”
Section: Introductionmentioning
confidence: 99%